Analysis Review on Performance Metrics for Extraction Schemes in Text Steganography - Raihan Sabirah Sabri; Roshidi Din; Aida Mustapha (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
In today's era of big data computer networks, protection of secret messages when transmitting information is a major concern. The openness and publicity of the communication channel are the main attraction for malicious people to steal personal data even though privacy protection in operational. Data extraction is process that reverses the data embedding process in information hiding. However, the performance of an information hiding framework highly depends on the evaluation metrics used. The effectiveness of evaluation itself is mainly determined by the performance aspect or critera such as capacity, imperceptibility or security. The aim of this paper is to present a review on trends for existing performance metrics used in extraction schemes from a data hiding framework. This review is hoped to help future research in evaluating the performance of data hiding framework in general and the proposed extraction schemes in specific.